Stability of Raise Bored Shafts in Australian Mines - M F. Lee (The Australasian Institute of Mining and Metallurgy, 2008)
In order to make good decisions, as to whether large diameter raise bored shafts can be constructed in blocky rock at a particular location, mine planners, management, geotechnical engineers and contractors must understand and consider a range of geotechnical issues. Firstly, mine management must ensure that adequate time and resources are available to find appropriate shaft sites. Deep weathering, adverse structures, groundwater, etc might mean that the most desirable location, with respect to other mine development, might not be suitable. Special site investigation drilling, etc may be necessary. Even then, alternative construction options might be necessary, other than just reaming through to the surface. A site investigation borehole should then be drilled to investigate specific and general ground conditions along the raise alignment. Often, only small sections of weak blocky rock dictate raise stability. While the empirical McCracken and Stacey method is typically used in Australia to assess raise stability and assess geotechnical risk, until recently it had no published performance data.An Australian database of raise performance now exists and is presented below, courtesy of an industry survey by the Eastern Australian Ground Control Group. Raise diameter and ground conditions (in terms of a lower bound Qr value) is presented for 50 cases versus raise performance.